The Essence of The Penalties in The Violation of The Civil War on Drugs in The City of Surakarta - Ersya Ananda Kusuma Wardani; Muhammad Rustamaji (PT. Anagata Sembagi Education, 2024)
This legal research aims to provide a study and analysis of the existence of fines and their role in overcoming narcotics crimes in Indonesia according to Law Number 35 of 2009 concerning Narcotics. This study uses a non-doctrinal or empirical legal research method that puts forward the function of direct research in the field with a qualitative descriptive approach. The data used in this study consisted of two types, primary and secondary. The primary data used consisted of observations at the Surakarta District Attorney's Office, while the primary data used were official documents, books, reports, and other literary sources. The results of the study indicate that fines are considered not effective in reducing the rate of narcotics crime in Surakarta City because the nominal amount of fines is very high, and is considered not to fulfill the purpose of punishment because of the lack of implementation that can be replaced by non-perpetrators and the threats that have not been received can not follow the development of currency values in society.